Possibility to Reduce Drudgery and Time in Harvesting Individual Ripe Fruits of Jatropha curcas Linn by Whole Bunch Harvesting - Jupikely James Silip; Armansyah H. Tambunan; Erliza Hambali; , Sutrisno; Memen Surahman (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2010)
<!– /* Font Definitions */ @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:Calibri; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:IN; mso-no-proof:yes; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> A study was conducted to determine Jatropha fruits ripening uniformity on its tree and bunches characteristics. To get more information about its ripening off, the tree characteristics a respiration pattern was determined. The data were collected on ﬁ ve trees for each ten selected accessions (n=50) for fruit ripening uniformity on its trees study and ﬁ fteen bunches for each seven selected accessions (n=105) for fruits bunches ripening uniformity study at two jatropha pilot projects at Sabah state of Malaysia at the end of March 2009 when the trees were exactly one year old. This study conﬁ rmed that heterogeneous ripening occured in all jatropha accessions and within individual jatropha bunches. Respiration tests conﬁ rmed that jatropha is a climacteric fruit. The results showed an upsurge in CO2 production at the end of ripening and at the beginning of senescence. This study has revealed indications of the possibility to harvest jatropha fruit in bunches rather than harvesting individual ripe fruit, which could potentially improve harvest efﬁ ciency by reducing harvesting time and drudgery. Keywords: ripening, respiration rate, post-harvest, climacteric